Recent Contributions to the Development of Barrel End-Mill Machining Technologies for Titanium Alloys in the Aerospace Context - Alina Bianca Pop; Sandor Ravai-Nagy; Aurel Mihail Titu; Nicolae Medan; Andrei Catalin Filip (Aerospace)
This study investigates the utilization of barrel end-mills in machining titanium alloys for aerospace applications. It involves a comprehensive review of the relevant literature and a preliminary experimental investigation, incorporating the influence of measurement direction on surface roughness and the behavior of cutting forces. The primary objective is to assess the performance and efficiency of these end-mills when machining challenging materials and to identify optimal cutting strategies. This paper emphasizes the significance of titanium alloys in the aerospace sector, due to their exceptional mechanical properties, and the problems encountered in their processing. It also highlights the advantages of barrel end-mills, such as enhanced accessibility and superior surface finish. Through a combination of literature review, practical experimentation under controlled conditions, and statistical analysis, this study investigates the surface roughness of the Ti-6Al-4V titanium alloy, confirming a significant difference between longitudinal and transverse roughness. The preliminary experiment revealed that the average values of longitudinal and transverse roughness were 0.237 µm and 0.263 µm, respectively. The coefficients of variation indicated a greater variation in longitudinal roughness (19.79%) compared to transverse roughness (18.61%). This study’s conclusions provide a solid foundation for future research into machining titanium alloys with barrel end-mills, contributing to the optimization of manufacturing processes and the enhancement of aerospace component performance.